STEPS IN THE MOVES OF KEYNOTE SPEECHES IN MOBILE PHONE LAUNCHING EVENTS AS POINTERS IN TEACHING PUBLIC SPEAKING (English Education Journal, 2012)
Pendekatan dalam genre menyarankan guru untuk menggunakan materi autentik dalam pengajaran sebagai salah satu terobosan yang berbeda. Sebuah Keynote speech adalah genre  yang mempunyai gerakan konstruktif yang spesifik di dalamnya. Step moving dalam keynote speech dibutuhkan sebagai penunjuk pada pengajaran public speaking untuk memberikan pendampingan kepada siswa untuk menyusun pidato. Latar belakang budaya dari dpeaker dan audience harus dipertimbangkan supaya keynote speech berkembang.Genre approach suggests teachers to use authentic materials in teaching as a kind of genre has different moves. A keynote speech is a kind of genre which has specific moves constructing it. Steps in the moves of a keynote speech are needed as pointers in teaching public speaking to give guidance for students in constructing a keynote speech. Cultural background of both the speaker and the audience should be put into consideration when a keynote speech is developed.